Development of Flipped Classroom Based Interactive Multimedia on Biodiversity Concept to Increase Students' Learning Motivation and Critical Thinking - Perta*, Hendro; Yulianti, Evy; Huang, Tzou-Chi (Jurnal Pendidikan Sains Indonesia, 2024)
Students' critical thinking skills are essential in 21st-century education. Certain students show a lack of enthusiasm for learning and have limited critical thinking skills. The aim of this study was to assess the impact of interactive multimedia in a flipped classroom setting on understanding biodiversity, with a particular focus on increasing learning motivation and critical thinking skills. The research employed a quasi-experimental method known as the nonequivalent control group design. Collecting samples using the cluster random sampling technique. The collection instruments include interviews, student needs questionnaires, validation questionnaires from media and material experts, learning objectives and teaching module flow questionnaires, teacher and student response questionnaires, learning motivation questionnaires, and critical thinking tests. Data analysis comes in a variety of forms, including initial study data analysis, feasible information analysis, practical information analysis, and effective information analysis. Feasibility has a score of 90.3% (very feasible), and practicality has a score of 91.2% (very practical). As well as the effectiveness of learning motivation with a sig. (2-tailed) of 0.000 0.05 and an N-Gain of 0.764 (high), besides critical thinking with a sig. (2-tailed) of 0.047 0.05 and an N-Gain of 0.706 (high). The research results show that interactive multimedia that utilizes the flipped classroom method is feasible, practical, and successful in increasing learning motivation and critical thinking skills. However, this interactive multimedia has only been implemented at senior high school 4 Muara Teweh, so it needs to be expanded to other schools and developed with other concepts